Depressive Experience of Chinese Young People During Travel: Emotional expression and social expectations from a cultural perspective - Wu,Xiran (2025)
In China, young people face intense academic competition, a competitive job market, and changing cultural narratives about success and stability. Travel is often seen by young people as a means of escaping these pressures, but it is also influenced by economic conditions, social class, and cultural capital. This paper seeks to explore how Chinese young people aged 18-35 view depressive experiences during travel at a cultural level, and how their travel experiences reflect the broader social and cultural attitudes towards the emotional health of new and younger generations in contemporary China. This study will combine Visual narrative analysis of travel-related pictures, videos, and posts published on social media. Personal narratives collected through interviews with students, graduates, employed and unemployed people, and people in the travel industry illustrate how travel challenges and strengthens the emotional health and life trajectories of contemporary Chinese youth.
Keywords: Chinese youth travel; mental health; social pressures; digital ethnography; visual narratives